Transformation of Communist Media Content and Public Space According to the Discourse ‘39Pact: Exiting the “Labyrinth” as an Act of Communication - Vaišnys, Andrius (Information & Media, 2020)
This text is about one of the longest processes of political communication, which, decades on, influences politicians of various generations of the Central, Eastern and Western Europe, contents of media and self-awareness of the audience. The process isn’t over yet, this is obvious not only from the document adopted by the EP but also from an international political rhetoric. Analysis of consequences of the Molotov-Ribbentrop Pact signed on 1939 in media (D’39Pact) and related national and international decisions is the axis of information conflict between the East and the West concerning thousands of fates. Those thousands of people had and still have different historical narratives – some people justified the Pact and implemented it, others were fighting for the elimination of its consequences, yet others fell victims to it, with a death toll estimated in the millions. But not everybody’s narratives are based on true arguments.Let’s look at the way the system of propaganda collapsed and the public opinion was transformed in countries of Central and Eastern Europe in 1988-1989. Moving from a lie to (hopefully) the historical truth. Review of consequences of the Molotov-Ribbentrop Pact was the main axis of such transformation (protection of environmental and cultural valuables, choice of one’s viewpoint, legislative requirements and other rights were contextual aspects of this axis). During this period in the previously mentioned region the control of public space was on the decline.This view will be based on a single thematic discourse: the provision of consequences of the 1939 Treaty of Non-aggression between Germany and the Union of Soviet Socialist Republics and criticism in communist model media of Lithuania and neighbouring countries. It may be called D’39Pact.D‘39Pact in general has several narratives (it may also be seen from the EP Resolution), but taking into consideration the interpretation of Jurgen Habermas’s Communicative Action, the analysis of transformation of 1988-1989 two of them would suffice, one of which is that of the authorities of the USSR and the other one – that of its opponents. Let’s call opponents USSR dissidents, protestors, underground press (samizdat) and press of public movements which was published legally.Narrative of the USSR authorities: the treaty was the inevitable and no annexes (secret protocols) exist.Narrative of the opponents: based on secret protocols of the treaty, the USSR and Nazi Germany divided the countries and destroyed their political, military, cultural elite and finally – their population of various social layers.Medias, as the main participant of the public space, most clearly disclose the collision of such narratives and transformation in D‘39Pact. The purpose of the article is to discuss the circumstances of transformation of MMPT from the historical perspective and of the public space and come across the factors, which influenced the strongest role of MMPT interpretative accomplishments. Considering the way out of the “labyrinth” regarding the D’39 Pact, we see some similarities with the situation that now exists in Russia.
Keywords: public space; mass media and propaganda tools (MMPT); discourse of 23 August 1939 (D‘39Pact); historical narrative; act of communication; the truth; resolution; political communication